Improving Agricultural Productivity and Market Efficiency in Latin America and the Caribbean : How ICTs Can Make a Difference? - Goyal, Aparajita; González-Velosa, Carolina (World Bank, Washington, DC, 2014)
Agricultural growth rates in the Latin America and the Caribbean (LAC) region have been much slower than the rest of the developing world. In the regions of East Asia, South Asia and Middle East and North Africa, the annual growth of agricultural Gross Domestic Product (GDP) in 1980-2004 exceeded 3 percent, while growth in Sub- Saharan Africa averaged almost 3 percent. This paper attempts to present an overview of the agricultural sector in LAC, discuss its distinctive features, and the potential role of Information and Communication Technology's (ICTs) in improving agricultural productivity and market efficiency in this region. The discussion in this paper will refer to the evidence provided by studies that evaluate the impact of ICTs interventions. While the emphasis will be put on the studies that evaluate interventions in the LAC region, there will also be references to studies in other developing economies whenever these are pertinent to the LAC context. The commercialization of agricultural products has suffered important transformations in recent decades, posing big challenges for farmers in the LAC region. Finally, the adoption of agricultural technologies will also be constrained by insecure land rights. Investing in technologies with long-run returns will not be attractive if farmers are uncertain about their property rights in the future (Jack, 2011). This is certainly an issue in several countries in LAC, where land conflicts, expropriation and de facto ownership are common.